Quiet voices : silence in the Hebrew Bible - Matthews, Victor Harold (Fortress Press, 2024)
"[This book] explores the language, context, and purpose of silence in the Hebrew Bible. It traces silence across the Bible's many genres (narrative, law, prophecy, psalmody, and wisdom) by using theoretical frames drawn from various academic disciplines (communication studies, political science, literary criticism, and sociological studies). The book examines how silence as a literary technique, particularly that of the narrator, connects theologically to themes of obedience, grief, hope, personal relationships, trauma, politics, and wisdom. The volume concludes with a theological reflection on the silence of God in the face of human suffering." --